З досвіду відбору науково-педагогічних кадрів на юридичний факультет Новоросійського університету (друга половина ХІХ – початок ХХ століття) - Таможська, Ірина Володимирівна; Tamozhska, Iryna Volodymyrivna (Мукачево : Мукачівський державний університет, 2017)
У статті висвітлено досвід Новоросійського університету щодо відбору науково-педагогічних кадрів в другій половині ХІХ – на початку ХХ століття на юридичний факультет. Встановлено, що основним джерелом заповнення вакантних посад на кафедрах юридичного факультету став інститут приват-доцентури. Акцентовано увагу на тому, що приват-доцентські кадри були резервом для комплектування майбутнього професорсько-викладацького складу. З’ясовано, що мало місце як об’єктивне, так і необ’єктивне ставлення до кандидатів під час виборів на вакантні посади, зокрема щодо оцінки їхнього науково-педагогічного досвіду та професійних якостей. Зазначено, що нерідко керівництво навчального закладу відмовляло претендентам у викладацьких посадах на основі ідеолого-політичних чинників. Відмічено, що на юридичному факультеті не вдалося створити систему викладання приват-доцентами навчальних курсів, паралельних професорським, які б мали скласти конкуренцію.

The development of the modern high legal education in Ukraine cannot happen without progressive, competitive scientific-pedagogical staff. Consequently, the deep analysis of the achievements and disadvantages of the scrutiny of the experience of pre-Revolutionary universities of Ukraine regarding the selection of scientific-pedagogical staff for the departments of Law Schools will have the significant contribution for the further modernization of the higher legal education. The author applied a method of archive materials research (reports of the academic council meetings and university reports, periodicals) and the theoretical methods of the pedagogical research (the analysis, generalization). The aim of the article is to reveal the experience of Novorossiysk University regarding the selection of scientific-pedagogical staff for the departments of Law Schools in the second half of the XIX – the beginning of the XX century. The experience of Novorossiysk University regarding the selection of scientific-pedagogical staff for the departments of Law Schools in the second half of the XIX – the beginning of the XX century is revealed in the article. It is defined that the main source of the filling vacancies at the departments of Law School was Privat-associate Professorship Institute. The attention is turned to the fact that the private associate professor staff was the fund for the filling of the future teaching staff. It is found out that both objective and non-objective attitude to applicants during the selection for the vacant posts occurred, especially regarding the assessment of their scientific-pedagogical experience and professional skills. It is noticed that the administration of the establishment often refused applicants in getting teaching posts on the basis of ideological and political reasons. It is indicated that the organization of the private-associate professors teaching system of the courses parallel to professors’ that could create competition failed. The carried out research gives the reason to prove that the problem of ensuring studying process at Law School by qualified scientific-pedagogical staff was solved through the engagement of private-associate professors to the teaching activity. The perspective for the further scientific research is the problem of scrutinizing human resource policies of Novorossiysk University at Medical School (1865 – 1917).
From the experience of selection of scientific and pedagogical staff to law faculty of Novo Russian university (second half of ХІХ – beginning of ХХ сentury)
Keywords: HUMANITIES and RELIGION; Новоросійський університет; юридичний факультет; приват-доценти; науково-педагогічні кадри; Novorossiysk University; scientific and pedagogical staf; Law School; private-associate professors